Students' Perceptions on Artificial Intelligence as Academic Support Among English Education Students at Batanghari University: A Case Study of ChatGPT - Aprilia, Dewi; Ismiyati, Yanti; Fitri, Nurul (Universitas Batanghari Jambi, 2025)
This research aims to analyze students' perceptions of AI-based learning among English Education students at Batanghari University. In an era where digital tools play an increasing role in education, understanding how students perceive artificial intelligence (AI) in the learning process becomes essential. This study adopts five key constructs to measure perceptions—engagement, interaction, satisfaction, academic performance, and behavioral intention—based on a validated framework by Khairuddin et al. (2024).The study employs a quantitative approach through a survey of 37 respondents from even-numbered semesters (2, 4, and 6). The questionnaire was distributed online and the data were analyzed using SPSS version 25. Statistical analysis included validity and reliability tests, descriptive statistics, normality and homogeneity tests, and hypothesis testing through One-Way ANOVA. The results revealed that students generally held a moderately positive perception toward AI-based learning. Among the five constructs, interaction received the highest average score, while behavioral intention had the lowest. Furthermore, the ANOVA test indicated a significant difference in students' perceptions across semester levels, confirming that academic experience influences how students view AI in learning. These findings suggest the importance of tailoring AI integration strategies based on students' academic maturity to maximize the effectiveness of AI tools in education.